Framework Development for Integrating Information and Communication Technologies Into The Ghanaian Senior High School Visual Art Curriculum - Degraft-Yankson, Patrique (2011)
A Dissertation Presented to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in Partial Fulfillment of the Requirements for the Degree of DOCTOR OF PHILOSOPHY IN ART EDUCATION, 2010